The IMPACT OF SUPEROXIDE DISMUTASE GENETIC POLYMORPHISM (SOD2 VAL16ALA) AND SUPEROXIDE DISMUTASE LEVEL ON DISEASE SEVERITY IN A COHORT OF EGYPTIAN SICKLE CELL DISEASE PATIENTS IN EGYPT - Mervat Khorshied; Iman Shaheen; Yasmeen Selim; Asmaa Elshahawy; Ilham Youssry (Mediterranean Journal of Hematology and Infectious Diseases, 2022)
Background: Oxidative stress plays a pivotal role in the pathophysiology of sickle cell disease (SCD) and its associated disease complications. Superoxide Dismutases (SODs) are protective enzymes against oxidative stress. SOD2 deficiency results in the accumulation of oxidized red cell proteins, increased rate of hemoglobin oxidation, decreased red cell membrane deformability, and subsequently decreased red cells survival. Objective: The current study was designed to determine the effect of SOD2 Val16Ala gene polymorphism (rs4880) on SOD2 level and their possible impact on SCD disease severity in a cohort of Egyptian SCD patients. Methods: Genotyping SOD2 Val16Ala polymorphism by TaqMan allelic discrimination assay for hundred SCD patients and a hundred age-sex matched healthy controls revealed the genotypic and allelic frequencies of the studied polymorphism in the SCD patients were close to that of the controls. Results: Serum SOD2 level was significantly lower in those having the polymorphic genotypes (p=0.005). SOD2 level inversely correlates with the annual rate of hospitalization (r=-0.023, p= 0.038). Conclusion: SOD2 Val16Ala polymorphism was associated with low serum SOD2 levels that may predict disease severity.